2003
DOI: 10.1023/a:1023483807731
|View full text |Cite
|
Sign up to set email alerts
|

Elevated risk of arrest for Veteran's Administration behavioral health service recipients in four Florida counties.

Abstract: This paper examines the relative contribution of mental and substance abuse disorders to criminal justice involvement by examining the relative risk of arrest for three groups of adult male recipients of VA behavioral health care services. These groups include men served for both substance abuse and mental health, for only substance abuse, and for only mental health. The relative risk of multiple offences is compared to relative risk of a single offense for each group. Results indicated that relative risk of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Overall, persons with severe mental illness have been found to comprise between 6% (males) and 15% (females) of the jail population, and approximately 60% of the mentally ill (depending on the gender and mental health diagnosis) have a current alcohol use disorder while one third have a current drug use disorder (Abram & Teplin, 1991). Studies of persons with dual disorders in community programs have found high rates of law enforcement involvement (Mueser, Essock, Drake, Wolfe, & Frisman, 2001;Pandiani, Rosenheck, & Banks, 2003).…”
Section: Co-occurring Disorders In Jailmentioning
confidence: 99%
“…Overall, persons with severe mental illness have been found to comprise between 6% (males) and 15% (females) of the jail population, and approximately 60% of the mentally ill (depending on the gender and mental health diagnosis) have a current alcohol use disorder while one third have a current drug use disorder (Abram & Teplin, 1991). Studies of persons with dual disorders in community programs have found high rates of law enforcement involvement (Mueser, Essock, Drake, Wolfe, & Frisman, 2001;Pandiani, Rosenheck, & Banks, 2003).…”
Section: Co-occurring Disorders In Jailmentioning
confidence: 99%
“…However, the mental health and substance use disorder treatment needs of female veterans in the justice system have not been a focus of attention in the research literature. Previous studies with justice-involved veterans excluded women 1,2 or did not examine women separately from men. 3 Although women are a minority among justice-involved veterans, with increasing numbers of women in the military 4 and in Veterans Health Administration (VHA), 5 as well as increasing rates of women from the general population entering the justice system, 6 it is plausible that the number of female veterans in the justice system will be expanding in the coming years.…”
mentioning
confidence: 99%
“…Compounding the relationship between mental illness and substance abuse for co-occurring populations is the question of how important is the relationship between mental illness and criminal justice involvement when controlling for substance abuse. Some scholars have found that the relationship between mental illness and criminal justice involvement disappeared when controlling for comorbid substance abuse (Pandiani, Rosenheck, & Banks, 2003;Quanbeck et al, 2005), a finding supported in another study involving veterans (Erickson, Rosenheck, Trestman, Ford, & Desai, 2008). Studies of this kind highlight the need for scholars to better understand the nature of these relationships between mental health status, homelessness, substance use, and criminal justice involvement.…”
Section: Introductionmentioning
confidence: 87%